RETURNING TO THE SCIENTIFIC PUBLICATION OF SARPEKOV R.K., K.YU.N., RAKHMETOVA S.M., D.YU.N., PROFESSOR «PROBLEMS OF BUILDING A PUNISHMENT SYSTEM IN THE CRIMINAL CODE OF THE REPUBLIC OF KAZAKHSTAN» - Karzhaubaev, Серик Сеитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The punishment system provides for a number of punishments from less severe to more severe. All these types of punishments have their positive and negative aspects, which affect their effectiveness. The article attempts to investigate the effectiveness of restriction of freedom as an alternative to imprisonment. Foreign experience, which is based on the introduction of this type of punishment, differs in its essence and purpose. In foreign legislation, this approach is presented in the form of probation, which aims to correct the convict and his socialization. Probation in foreign legislation is a security measure, not a punishment. Therefore, when appointing probation, the court gives certain opportunities to avoid the use of a more severe type of punishment. In its purpose, probation is very similar to probation, which operates in national criminal law. Logically, the question arises about the expediency of applying restrictions on freedom, since there are other fairly effective means of combating crime, such as probation. The improvement of these mechanisms will make it possible to avoid the use of punishment in the form of restriction of freedom. Moreover, the exclusion of restriction of freedom as a form of punishment will solve a number of important problems. First, a correct understanding of the international experience in the use of probation, which is fundamentally different from the use of restriction of freedom as a form of punishment in Kazakhstan. Secondly, the exclusion of the corruption component, which consists in the possibility for the court to appoint restriction of freedom as a legitimate alternative to imprisonment. This is the problem of applying punishment that excludes the punitive element. Third, the expansion of the possibility for the use of probation as a sufficiently effective measure for the prevention of offenses. The similarity of restriction of freedom and probation makes it necessary to reconsider the question of the expediency of restriction of freedom.